ROUTE BREAKAGE CONCERNED NON INTERFERING MULTI PATH ROUTING PROTOCOL FOR WIRELESS SENSOR NETWORK - N Sudhakar, J Avinash (International Journal of Advanced Science and Technology, 2019)
Interference avoided routing is more difficult task in the Wireless Sensor Network (WSN) where there is no centralized node to monitor the ongoing data transmission. This is focused and handled in the previous work via using the technique called Interference Reduction aware Optimal Routing Scheme (IRORS). However this work doesn’t focus on intermediate path breakages which might affect the successful data transmission. Path breakage prediction during run time is more difficult where the uninterrupted data transmission is more complex. This is handled in the proposed work through enhancing the technique called as Route Breakage concerned Non-Interference Multipath Routing Protocol (RB-NIMRP). In this work, reliable faster data transmission is guaranteed by introducing the non interfering multi path selection method. Through this multiple route paths data transmission will be performed. And then these route paths will be monitored dynamically in terms of their individual nodes resources. In terms of lacking resources immediately rerouting will be done before path failure. Here monitoring node is responsible for finding the node failures which should be selected more optimally. This is done with the help of dynamic monitor node selection process. Upon finding route path breakage possibility due to resource lack or malicious node presence, in this work immediate rerouting will be performed. The overall estimation of the proposed work is executed in the NS2 simulation environment and it is demonstrated that the proposed method tends to provide better performance than existing work.